1974
DOI: 10.1161/01.cir.49.4.599
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Complications of Coronary Arteriography

Abstract: (1) Death or the serious nonfatal complications of myocardial infarction and/or cerebral embolus occur in an unacceptable 1.5% of all patients examined; the occurrence is ten times higher in institutions performing fewer than 100 examinations/year than in those doing more than 400/year. Reported death rates vary more than one hundred fold, from 0.05% to 8%.1, 2 (2) The serious complications, primarily thrombotic, occur eight times more frequently when the percutaneous transfemoral approach is used. (3) Fifty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(32 citation statements)
references
References 3 publications
2
30
0
Order By: Relevance
“…10 The IVUS system was the Clear View Ultra with Automatic Pullback Device and Ultra Cross 3.2 F -30 MHz catheters (Boston Scientific, USA). A standard dose of intracoronary nitrate (100-200 mcg) was administered before acquisition of images.…”
Section: Ivusmentioning
confidence: 99%
“…10 The IVUS system was the Clear View Ultra with Automatic Pullback Device and Ultra Cross 3.2 F -30 MHz catheters (Boston Scientific, USA). A standard dose of intracoronary nitrate (100-200 mcg) was administered before acquisition of images.…”
Section: Ivusmentioning
confidence: 99%
“…Another smaller report from approximately the same time in patients undergoing femoral coronary arteriography from Walker et al [5], showed a 17.8% incidence of thromboembolic complications in patients not given systemic heparin compared to 1.3% in those who received anticoagulation. Shortly after the release of these reports, Judkins and Ganden [6] editorialized that systemic anticoagulation with heparin should be routinely used during coronary arteriography to counteract the inherent thrombogenicity of the guidewires and catheters utilized, particularly with the femoral technique.…”
Section: Factors Related To Thrombosis During Coronary Angiography Anmentioning
confidence: 99%
“…The incidence of major thromboembolic complications in early reports varied widely from 0.05% to 8% [2,11]. In a 1974 editorial, Judkins and Gander implicated a variety of possible factors: i.e., the catheterization route (brachial versus femoral), the coagulation status of the patient (use of systemic heparinization), operator experience and duration of the procedure [2]. The Society for Cardiac Angiography and Interventions presented data on 222,553 patients collected in their registry between July 1984 and December 1987 [ 121.…”
Section: Discussionmentioning
confidence: 99%